Choose the Right Citrus Rootstock - William S. Castle; Stephen Futch; Rhuanito Soranz Ferrarezi (EDIS)
After the arrival in 2005 of citrus greening disease or Huanglongbing in Florida, making a profitable rootstock decision became more complicated.  New rootstocks are being developed and released for commercialization at an accelerated pace.  Regardless of these changes, there remains a time-honored framework for selecting rootstocks. This publication provides guidance in 4 aspects of scion selection: site history, objectives, sources of information on rootstocks, and choosing a rootstock that matches site and grower objectives. https://edis.ifas.ufl.edu/hs178